Mesenchymal Stromal Cells as Critical Contributors to Tissue Regeneration - Sagaradze, Georgy D.; Basalova, Nataliya A.; Efimenko, Anastasia Yu.; Tkachuk, Vsevolod A. (Frontiers in Cell and Developmental Biology, 2020)
Adult stem cells that are tightly regulated by the specific microenvironment, or the stem cell niche, function to maintain tissue homeostasis and regeneration after damage. This demands the existence of specific niche components that can preserve the stem cell pool in injured tissues and restore the microenvironment for their subsequent appropriate functioning. This role may belong to mesenchymal stromal cells (MSCs) owing to their resistance to damage signals and the potency to be specifically activated in response to tissue injury. Accumulated evidence has established the critical role of MSCs in tissue regeneration after injury. This is confirmed by the promising results of the application of MSCs or MSC-derived products for the treatment of different injuries. However, in some cases, the potency of such products may be limited by the functional alterations of these cells. In particular, senescence of MSCs causes crucial impairment of their regenerative capacity and functional persistence determined by the native microenvironment. Considering MSCs as critical contributors that preserve a pool of stem cells and restore a stem cell niche after injuries, we conclude that for the effective stimulation of tissue regeneration, it is extremely important to understand how to manage the tissue-specific interactions between MSCs and niche cells. Based on literature data and our own results, we integrate the current ideas on the contribution of MSCs in restoring the stem cell niche after damage and thereby tissue regeneration.